Perancangan Jaringan Sub Carrier Multiplexing (SCM) / Wavelength Division Multiplexing (WDM) Radio Over Fiber (ROF) Menggunakan Teknik Modulasi DPSK - D, Dyan Anggreani; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The rapid development of telecommunications technology makes a network with a larger bandwidth capacity and higher speed. In order to meet these demands, optical communication technologies have been developed, one of which is Radio Over Fiber (RF), which combines a wireless and an optical network using an analog optical cable that transmits a modulated Radio Frequency (RF) signal. This study uses a frequency of 15 GHz combined with Wavelength Division Multiplexing (WDM) and Sub Carrier Multiplexing  (SCM) technology. It presents an SCM/WDM ROF using Diferensial phase shift keying  (DPSK) modulation technique. The performance parameters are BER, Q-factor and eye diagram. The model system was simulated using the OptiSystem simulation software. Based on the results, the BER values are 1.00243 x 10-50 at SCM/WDM 1 and 1.24638 x 10-47 at SCM/WDM 2, respectively. Futhermore, the Q-Factor quality is 14,933 at SCM/WDM 1 and is 14,4503 on SCM/WDM 2. All parameters are in accordance with ITU standardization.  Keywords: DPSK, Eye Diagram, OptiSystem, ROF, SCM, WDM,  Q-Factor